2020
DOI: 10.1093/jscr/rjz382
|View full text |Cite
|
Sign up to set email alerts
|

Gastric schwannoma: a diagnosis that should be known in 2019

Abstract: Gastric schwannoma (GS) is a rare neoplasm of the stomach deriving from Schwann cells of the peripheral nerves in the stomach. It accounts for 0.2% of all gastric tumors and is mostly benign, slow-growing and asymptomatic. Due to its rarity, GS is not widely recognized by clinicians. Preoperatively, GSs are difficult to differentiate from other mesenchymal tumors, such as gastrointestinal stromal tumor (GIST) or leiomyoma, which develop from mesenchymal stem cells. The optimal management of GS is based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In CT examination, GS usually shows a clear oval tumor under the gastric mucosa, with an exogenous or mixed growth mode, moderate uniform, or moderate progressive enhancement. Most surrounding lymph nodes do not appear to be enlarged [ 13 ], there might be a few of the enlarged perigastric lymph nodes seen that are reactive inflammatory lymph nodes [ 14 ]. Hong et al reported their findings after examining 16 cases of GS at their institution on CT scans, of which 13 cases (81%) showed uniform enhancement [ 15 ], and they were all prominent growths, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In CT examination, GS usually shows a clear oval tumor under the gastric mucosa, with an exogenous or mixed growth mode, moderate uniform, or moderate progressive enhancement. Most surrounding lymph nodes do not appear to be enlarged [ 13 ], there might be a few of the enlarged perigastric lymph nodes seen that are reactive inflammatory lymph nodes [ 14 ]. Hong et al reported their findings after examining 16 cases of GS at their institution on CT scans, of which 13 cases (81%) showed uniform enhancement [ 15 ], and they were all prominent growths, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…GS shows positive staining for S100, vimentin, Leu-7, glial fibrillary acidic protein (GFAP), myelin-associated glycoprotein, and nonspecific enolase while desmin, CD117, striated muscle actin, smooth muscle actin, and myosin stain negative on immunohistochemistry [ 1 , 6 , 8 ]. Peritumoral lymphoid cutoff is another feature that helps to differentiate GS from GIST [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these options, complete surgical excision of the tumor is considered as the gold standard for the management of GS. Endoscopic resection is another treatment option that have been described recently but is limited by the tumors > 3 cm and location within the muscularis propria as it usually requires surgical excision because of increased risk of perforation [ 6 , 8 , 9 , 10 ]. This was the case in our patient who underwent complete surgical resection due to tumor size of 4.2 cm and location in the muscularis propria.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the seriesthere is a slight female predominance [4][5][6].The GS is usually in the form of an isolated lesion and is usually localized in the body of the stomach [7,8].…”
Section: Case Reportmentioning
confidence: 99%